Grain yield and protein content in winter wheat grain under the influence of retardants on different nutrient backgrounds in the eastern forest-steppe of Ukraine (Journal “Crop Production, Selection And Seed Production, Fruit And Vegetable Growing”, 2026)
This paper presents the results of a two-year study on the effect of seed treatments with growth retardants, under various urea fertilization regimes, on grain yield, grain protein content and protein yield per hectare in winter wheat of the Bogdana variety. Formulation of the problem. One of the factors contributing to reduced grain yields in cereal crops is plant lodging, which occurs primarily when high doses of nitrogen fertilizers are applied to well-moistened soils. As a result, grain yields can be reduced by up to 40% or more. Consequently, it is essential to identify ways to address the problem of lodging. In this regard, the most effective approach is the treatment of crops with growth retardants, which, alongside effectively solving the problem of lodging, promote accelerated plant growth and development, enhance their adaptive properties to stress, and ensure the full realization of the genetic potential for crop productivity. Therefore, the use of growth retardants is promising and requires further study, both to identify the best products and to develop algorithms for their application.The aim of the study was to compare the effectiveness of modern retardants with different active ingredients, under various mineral nutrient conditions, on the grain yield and protein content of winter wheat in the Eastern Forest-Steppe region of Ukraine.Research methods. The experiment was set up using the split-plot design. The main plots comprised four variants of fertilization with different doses of urea during the 22nd–23rd microphase: 1 – control; 2 – 75 kg/ha (N35); 3 – 108 kg/ha (N50); 4 – 141 kg/ha (N65). The second-order plots comprised five treatments involving the application of growth retardants to the crops during the 31st microphase: I – control (no growth retardants applied); II – Moddus Star; III – Retacel 720; IV – Medax TOP; V – a mixture of Moddus Star + Retacel 720. The area of the experimental plot was 37.5 m², and that of the reference plot was 30 m². Results. In terms of its effect on grain yield, the treatment with the growth regulator Medax TOP proved to be the most effective in the trial. The average grain yield in this treatment was 5.19 t/ha, which is 7.2 % higher than in the control. Under the weather conditions of both years, a significant increase in grain yield was also observed in the treatment option using a mixture of Moddus Star and Retacel 720 retardants. Thus, in 2024 and 2025, grain yield in this option averaged 4.36 and    5.76 t/ha respectively. It was on a par with the option involving the application of the Medax TOP retardant, significantly exceeding the other options. Overall, the highest winter wheat grain yield was observed in the treatment involving the application of 141 kg/ha of urea (N65) during the 22nd–23rd microphase, combined with spraying the crops with the growth regulator Medax TOP during the 31st microphase. In 2024 and 2025, it amounted to 4.27 and 6.27 t/ha respectively, which is 1.16 and 1.58 t/ha higher than in the control treatment. However, it did not differ signi-ficantly from the grain yield in the treatment involving the application of 108 kg/ha of urea (N50). Based on this, the best option in the trial was to fertilize the crops with urea at a rate of N50 in combination with spraying the crops with the retardant Medax TOP. The application of growth retardants to crops had virtually no effect on the protein content of the grain. There was only a slight tendency for it to increase when crops were sprayed with the retardants Medax TOP and Moddus Star. Specifically, on average across years and urea fertilization treatments, the protein content in the treatments where these products were applied was 14.0 %, whereas in all other treatments it was 13.9 %. The highest protein yield was observed in the variant where urea was applied at a rate of 141 kg/ha in combination with treatment of the crops with the growth retardant Medax TOP. In 2024 and 2025, it amounted to 0.684 and 0.865 t/ha respectively, which is 38.5 and 40.9 % higher than in the control. At the same time, virtually the same protein yield was observed in the variant where 108 kg/ha of urea was applied. Conclusions. The results of two-year studies demonstrated the high effectiveness of spraying crops with retardants during the 31st microphase under all urea fertilization regimes. In terms of grain yield, protein content in the grain and protein yield per hectare of Bogdana winter wheat, the best option in the trial was the treatment of crops with the Medax TOP retardant against a background of urea fertilization during the 22nd–23rd microphase at a dose of 108 kg/ha (N50).
Keywords: winter wheat; grain yield; growth retardants; fertilization regime; growth stages; top dressing; grain quality; protein content